THE RENAISSANCE NOMENCLATURE OF THE FASTI CONSULARES - Damiano Acciarino (Journal of Ancient History and Archaeology, 2018)
In 1546 one of the most important archaeological discoveries of the Renaissance took place, the so-called Fasti consulares, panels upon which were engraved the succession of Roman magistrates. These epigraphs were named in several ways, reflecting how they were understood by the scholarly community and what their reception would be, given the growing sensitivity to artefacts from antiquity. Their nomenclature was problematic from the very beginning. Only the thorough cross-referencing of textual and material sources could provide a term which eventually expressed their real essence. The purpose of this study is to reconstruct the phases that brought this find to acquire the denomination of fasti in early modern times, and to discover what precisely contributed to this choice.